Influence of cellulose ether polymers on ketoprofen release from hydrophilic matrix tablets - Vueba, M. L. (2004)
The present work reports the study of different ketoprofen:excipient formulations, in order to determine the effect of the polymer substitution and type of diluent on the drug-release mechanism. Substituted cellulose--methylcellulose, hydroxypropylcellulose and hydroxypropylmethylcellulose were used as polymers, while lactose monohydrate and [beta]-cyclodextrin were tested as diluents. Distinct test formulations were prepared, containing 57.14% of ketoprofen, 20.00% of polymer, 20.29% of diluent, and 1.71% of talc/0.86% of magnesium stearate as lubricants. The tablets were tested for their drug content, weight variation, hardness, thickness, tensile strength, friability, swelling and release ratio. Polymers MC25 and HPC were found not to be appropriate for the preparation of modified release ketoprofen hydrophilic matrix tablets, while HPMC K15M and K100M showed to be advantageous. The analysis of the release profiles in the light of distinct kinetic models (zero-order, first-order, Higuchi and Korsmeyer-Peppas) led to the conclusion that the type of polymer did not influence the release mechanism of the drug. The mean dissolution time (MDT) was determined, the highest MDT value being obtained for HPMC formulations. Moreover, the drug-release process was found to be slightly influenced by the type of diluent, either lactose or [beta]-cyclodextrin.